2012
DOI: 10.1371/journal.pone.0040974
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Mapping and Identification of Candidate Genes for the Rumpless and Ear-tufted Traits of the Araucana Chicken

Abstract: Araucana chickens are known for their rounded, tailless rumps and tufted ears. Inheritance studies have shown that the rumpless (Rp) and ear-tufted (Et) loci each act in an autosomal dominant fashion, segregate independently, and are associated with an increased rate of embryonic mortality. To find genomic regions associated with Rp and Et, we generated genome-wide SNP profiles for a diverse population of 60 Araucana chickens using the 60 K chicken SNP BeadChip. Genome-wide association studies using 40 rumples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 30 publications
3
34
0
2
Order By: Relevance
“…Although IRX4 does not fall within the defined critical region, it is within the same genomic cluster as IRX1 and IRX2 [31], [55]. IRX4 expression is restricted primarily to the heart at these stages, suggesting that the regulatory elements controlling its expression are not as closely shared as for IRX1 and IRX2 [55], [56], [57], [58].…”
Section: Resultsmentioning
confidence: 95%
“…Although IRX4 does not fall within the defined critical region, it is within the same genomic cluster as IRX1 and IRX2 [31], [55]. IRX4 expression is restricted primarily to the heart at these stages, suggesting that the regulatory elements controlling its expression are not as closely shared as for IRX1 and IRX2 [55], [56], [57], [58].…”
Section: Resultsmentioning
confidence: 95%
“…In chickens, many genome-wide association studies (GWAS) were conducted using the Illumina 60K SNP Beadchip. Using this method, major loci associated with growth (Gu et al, 2011;Xie et al, 2012), egg production Wolc et al, 2012), rumpless and ear-tufted traits (Noorai et al, 2012), body composition and meat quality (Liu et al, 2013), resistance to Marek's disease (Li et al, 2013), and immune responses to Newcastle disease virus (Luo et al, 2013) were identified.…”
Section: Introductionmentioning
confidence: 99%
“…In chickens, GWASs have been used to identify major loci associated with growth (Gu et al 2011;Xie et al 2012), egg production (Liu et al 2011;Wolc et al 2012), rumpless and ear-tufted traits (Noorai et al 2012), body composition and meat quality , resistance to Marek's disease ) and immune response to NDV (Luo et al 2013). However, these studies were carried out using SNP chips.…”
Section: Introductionmentioning
confidence: 99%